A novel method for detecting moldy pear core based on CEEMDAN decomposition and reconstruction of VAVN signals with data-level fusion - Kang Zhao; Yunhao Zhang; Wenbo Fu; Jie Liu; Shuhui Bi; Han Zhang; Tao Shen (Food Control, 2027)

Facilitating community-based biocultural stewardship into transformative change: an ethnobiological perspective - Yao Fu; Prateep Panyadee; Yinxian Shi; Yingfeng Bi; Xuefei Yang (Current Opinion in Environmental Sustainability, 2026)

New polyoxygenated fatty acid ester and other constituents from Dendrobium nobile Lindl. and their chemotaxonomic significance - Ting Chen; Dan Zhang; Xiujuan Fu; Siwei Chen; Hui Lei; Xiaoxu Bi (Biochemical Systematics and Ecology, 2026)

GPR75 mediates hyperuricemia-induced endothelial inflammatory injury via a HOTAIR/miR-141-3p regulatory network - Jiawu Fu; Junbing He; Keshen Li; Manting Zhang; Jiekai Li; Yuchun Liu; Yusen Chen; Wei Bi (Molecular Biology Reports, 2026)

Endophytic fungi mediate litter decomposition dynamics through microbial interactions and temporal shifts - Yuan-Qi Zhao; Fu-Sen Nan; Xiao-Qian Yang; Jian-Fei Yu; Han-Yue Bi; Si-Jun Duan; Xin-Yue Wang; Tian-Ci Chen; Qin-Jiang Mao; Xiao-Bo Wang (Soil Biology and Biochemistry, 2026)

Constructing a “switch” for photo-thermal catalytic pathway: Directional regulation of NO reduction product distribution by the coordination mode at the La site over Pd–La/CeO2 - Jianfei Li; Boxiang Du; Qian Xia; Zhuoran Bi; Xiangyu Meng; Jinlin Long; Zizhong Zhang; Wenxin Dai; Xianzhi Fu (Chemical Engineering Journal, 2026)

Mechanism of hardpan remolding furrowing for alfalfa based on a shear-resistant reversible bonding model - Lei Liu; Yubin Bi; Zuoli Fu; Zhengdao Liu; Zhiqi Zheng; Hongbo Zhao; Yuxiang Huang (Soil and Tillage Research, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

Quantifying responses of concurrent PM2.5-O3 pollution to their precursors in the Yangtze River Delta megacity Cluster of China - Mingliang Ma; Mengjiao Liu; Mengnan Liu; Yihong Jiao; Fei Meng; Pingjie Fu; Jingxue Bi; Tongshuai Rong; Yangyang Liu; Yuqiang Wang; Huaqiao Xing (Environment, Development and Sustainability, 2026)

Caledonian intracontinental metallogeny in South China - Ruizhong Hu; Mingliang Huang; Jiantang Peng; Jiehua Yang; Shanling Fu; Xianwu Bi (Science China Earth Sciences, 2026)

Heterojunction interfacial Mo − S bond induced directional electron transport enables efficient visible-light-driven hydrogen evolution - Yidong Pan; Yufeng Fan; Yang Fu; Zhichao Deng; Muhammad Sohail Riaz; Hong Li; Weiju Hao; Jinchen Fan; Guisheng Li; Qingyuan Bi (Chemical Engineering Journal, 2026)

Numerical Investigation of Time-Dependent Deformation and Fracture Evolution in Flawed Sandstone - Teng-Fei Fu; Zhu-Guang Wang; Bi-Bi Qiao; Ya-Tao Li; Tao Ding; Chong-Feng Chen (Geotechnical and Geological Engineering, 2026)

Advances in carrier-free nanodrug delivery systems - Jin-Ye Liu; Yan-Yan Zheng; Shu-Yu Wang; Yan-Ping Bi; Ming-Shuang Sun; Ji-Fu Hao; Yu-Jing He (Drug Delivery and Translational Research, 2026)

Linkage regimes of China's ecological engineering projects with the progress of sustainable development goals - Jia Bi; Fengchen Liu; Fu Li; Deyong Yu (Applied Geography, 2026)

Characterization of Viable and Non-viable Microbes in PM2.5 at a Mountain Site in Southern China - Yu Zheng; Senchao Lai; Zhaokang Ruan; Yuhong Feng; Yuhan Shen; Yaoyao Fu; Xinhui Bi; Dingli Yue; Zhifeng Shi; Yingyi Zhang (Aerosol Science and Engineering, 2026)

Performance optimisation of self-cleaning devices and activity level analysis of elastic balls based on simulation - Yubin Bi; Qingbin Song; Hongtu Liu; Jintao Feng; Yuxiang Huang; Zuoli Fu; Jixing Zhou (Biosystems Engineering, 2026)

Insights into saltiness enhancement effect and processing stability of pea-derived peptides using psychophysics and molecular docking - Anzhen Fu; Yixin Dai; Fan Yang; Qinghui Jia; Ye Liu; Shuang Bi (Food Research International, 2026)

Harvesting reed (Phragmites australis) for wetland nitrogen removal: Productivity, microbial communities, and underlying mechanisms - Junli Wang; Yucui Bi; Zishi Fu; Hongxia Qiao; Fuxing Liu (Bioresource Technology, 2026)

Canonical Wnt pathway mediates catalpol-induced epithelial differentiation of porcine metanephric mesenchymal cells - Pengcheng Ji; Yuansheng Xie; Guangrui Geng; Wenkai Guo; Jingru Bi; Bing Han; Xu Wang; Bo Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Hydrodynamic impacts of floating-raft aquaculture in the northern yellow sea: modeling and field experiments - Xiaomeng Fu; Jie Tian; Ming Li; Yuan Zhang; Junru Guo; Jun Song; Yang Ding; Congcong Bi (Ocean Dynamics, 2026)

Decoding salty peptides from pea protein: Isolation, characterization, and structure-activity relationship - Anzhen Fu; Jingzhe Sun; Shaobo Zhen; Fan Yang; Huanlu Song; Jinhua Zuo; Xiaoyan Zhao; Ye Liu; Shuang Bi (Food Chemistry, 2026)

Sustainable valorization of shield tunneling spoil via silane-coupled recycled mask fibers: Interfacial enhancement and engineering performance - Yu-Zhang Bi; Xin-Po Sun; Chun-Ying Wang; Tian-Xing Ma; Xian-Lei Fu; Zhe-Yuan Jiang (Sustainable Chemistry and Pharmacy, 2026)

Design and activity validation of GABA-gated chloride channels allosteric modulators based on computational biology - Siyi Yang; Shuang Gao; Tiansong Li; Jinghu Bi; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Pea protein: Advances in applications, protein-flavor interactions, and flavor enhancement strategies - Anzhen Fu; Liya Liu; Xiaoying Xiong; Jinhua Zuo; Yanbo Wang; Ye Liu; Shuang Bi (Food Research International, 2026)

Structural vibration analysis and safety assessment of centrifuges under hypergravity environments - Chengpeng Hong; Guanwen Liang; Li Bi; Haoran Fu; Zizhuang Yan; Kuigen Lin; Yunmin Chen (Engineering Structures, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

Assessing the performance of a surface washing agent for oil removal from sand in cold environments - Jiyao Sui; Huifang Bi; Rengyu Yue; Haiyan Fu; Aili Yang; Chunjiang An (Marine Environmental Research, 2026)

Strategy for doubling the yield of phenolics in hydrothermal liquefaction of Arundo donax: mechanistic study on weak alkaline catalyst suppressing hydrochar formation and enriching phenolics in aqueous and biocrude phases - Lei-ming Bi; De-lin Fu; Xian-shuai Fu; Li-hui Zhang; Feng Duan (Biomass and Bioenergy, 2026)

Interaction mechanisms of seed suction and cleaning negative pressure of an air-suction seed metering device for maize breeding plots - Pengfei Zhao; Qingbin Song; Yubin Bi; Jianxin Dong; Zuoli Fu; Yuxiang Huang; Yi Zheng (Biosystems Engineering, 2026)

Contaminant migration in vadose zone beneath unregulated landfills with damaged geomembranes - Yu-Zhang Bi; Xin-Po Sun; Qi Zou; Zhe-Yuan Jiang; Xian-Lei Fu (Waste Management, 2026)

Application of nano-selenium and glutathione with pyrimethanil enhance cucumber resistance to Botrytis cinerea by boosting root secretion and recruiting beneficial microorganisms - Yujiao Jia; Lu Kang; Ping Wang; Tong Wu; Xiaorui Fu; Xiaoying Wan; Tingjie Huang; Xiangzhong Wei; Xi Wang; Yaling Bi; Canping Pan (Chemical Engineering Journal, 2026)

Synergistic Neuroprotection of Combined Shenmai and Hypothermia in Cerebral Ischemia–Reperfusion Injury via ERK-Dependent Anti-inflammatory Effects - Yuan Wang; Hangui Ren; Yufei Qiu; Rongchen Dai; Mengfan Liu; Shiting Mo; Yibo Zhang; Wang Fu; Qianqian Bi; Yongpeng Wang; Yunuo Zhou; Zhichao Xi; et al. (Molecular Neurobiology, 2026)

Secukinumab improves pregnancy outcomes in recurrent spontaneous abortion with T helper 17 cells/T regulatory cells imbalance: a retrospective cohort study - Guihua Zhu; Xue Wang; Shuqin Bi; Juan Liu; Guiling Yuan; Ning Li; Jinhua Fu; Long Zhao (European Journal of Clinical Pharmacology, 2026)

Characterizing the marine recreational fishery of Hong Kong using data compiled from a social media platform - Bi Wei Low; Hilton H.C. Fu; Harris C.Y. Poon; Alex H.B. Liu; Heok Hui Tan; Kelvin K.P. Lim; Anthony Lau (Regional Studies in Marine Science, 2025)

Dual role of functional bacterial agent based on Bacillus subtilis coupled with smooth vetch (Vicia villosa var.) on cadmium-contaminated soil: Synergistic passivation and nutrient supply - Qiwen An; Jie Liu; Yitong Liu; Fuxuan Bi; Zonghao Dong; Xu Liu; Zhao Jiang; Libo Fu; Hongli Fan; Jianhua Qu; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

Carbon source shaped microbial ecology, metabolism and performance in biofilm system for simultaneous phosphorus recovery and nitrogen removal - Zhen Bi; XueLing Wang; Hao Fu; Yong Huang (Environmental Research, 2025)

Intrinsic kinetics study of microwave catalytic pyrolysis of cellulosic biomass using a novel microwave thermogravimetric analyzer - Qing An; Leon Fu; Xiaotao Bi (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Quantitative estimation of the spatiotemporal responses of PM2.5 and O3 synergistic pollution to precursors in the Chengdu-Chongqing City Group of China - Mingliang Ma; Yihong Jiao; Mengjiao Liu; Mengnan Liu; Fei Meng; Huaqiao Xing; Jingxue Bi; Yuqiang Wang; Tongwen Liu; Pingjie Fu (Air Quality, Atmosphere & Health, 2025)

A mechanistic perspective: How does tert-butylhydroquinone retain antioxidative efficacy in edible oils during storage? - Mengqi Xu; Yaxing Yu; Jun Li; Yanlan Bi; Jun Liu; Chenyu Fu (Food Chemistry, 2025)

Smart dual-channel fluorescent sensor overcoming cross-interference: Visual detection of Cu(II) and doxycycline in multiple scenarios, and precise discrimination of tetracycline analogs - Yingqi Yuan; Liuqing Fu; Lina Zhang; Jun Xu; Ning Bi; Yongxin Li; Lei Jia (Chemical Engineering Journal, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Characterization of phenethyl isothiocyanate nanoemulsion loaded pectin/chitosan composite film and application in beef preservation - Xiaojing Ma; Jiachen Lv; Jiale Fu; Hongshun Hao; Jingran Bi; Hongman Hou; Gongliang Zhang (Food Chemistry, 2025)

Comprehensive insights into the mechanisms influencing flavor alteration in mutton soup induced by thermal and cold sterilization: Integration of flavoromics and lipidomics - Chunyuan Ping; Xiaoping Li; Tianyang Wang; Bowen Zan; Xingyou Chen; Fu Wang; Jicai Bi; Xiang Li (Food Chemistry, 2025)

Emerging role of RNA m6A modifications in laryngeal squamous cell carcinoma: insights into tumorigenesis and therapeutic potential - Guotong Zheng; Jing Bi; Yangyan Yan; Bo Yu; Yong Fu (Apoptosis, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Research on the effects of split injection on diesel engine spray impingement and fuel film under cold-start conditions - Jie Yan; Luxin Fu; Weizheng Zhang; Xu He; Shuang Jin; Zhenyao Guo; Huahong Yu; Sinan Bi (Fuel, 2025)

Characterization of key aroma compounds in Maillard reaction products of Agrocybe aegerita enzymatic hydrolysates by GC×GC-O-MS - Hongyang Meng; Fan Yang; Shaobo Zhen; Anzhen Fu; Shuang Bi; Ye Liu (Food Bioscience, 2025)

A recyclable magnetic polyethyleneimine-functionalized cellulose aerogel for reducing cadmium (Cd) accumulation in acidic contaminated soil: Stress mitigation and soil improvement mechanisms - Fuxuan Bi; Zhao Jiang; Zhiyu Zhang; Zhan Zhang; Mengning Wang; Libo Fu; Hongli Fan; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2025)

An empirical exploration of the capacity of choline chloride/lactic acid eutectics to extract and stabilize natural polyhydroxy compounds - Yanhong Bi; Ruiping Fu; Weiliang Hua; Xinyu Xiong; Chun Zhu; Xiaobao Nie; Zhaoyu Wang (Food Chemistry, 2025)

Eutrophication‐induced dinoflagellate succession contributes to marine carbon sequestration through refractory dissolved organic matter accumulation - Fu‐Tao Fang; Zhuo‐Yi Zhu; Yuan‐Bi Yi; Ding He; Hong‐Yan Bao; En‐Ren Zhang; Cheng‐Xu Zhou (Limnology and Oceanography, 2025)
The increasing eutrophication of coastal seas is causing a shift in the most important phytoplankton groups from diatoms to dinoflagellates, but its feedback to marine carbon cycling remains unclear. Here, we investigated the potential of the key coastal phytoplankton, the diatom Skeletonema costatum , and the dinoflagellate Prorocentrum donghaiense , for refractory dissolved organic carbon (DOC) accumulation over dark degradation incubations of 70 d. Our multi‐method approach showed that dinoflagellate detritus, rather than diatom detritus, significantly contributes to refractory DOC. This is evidenced by the fact that the detritus of dinoflagellates compared to that of diatoms (1) has a weaker transmittance in infrared spectrometry, indicating a lower content of labile organic substances (alcohol and amide groups); (2) has a higher release and/or transformation efficiency of particulate organic carbon to DOC (81% vs. 50%); (3) has a lower content of labile fraction, amino acid (8% vs. 17% carbon) and exhibits lower degradability of the DOC formed (23% vs. 30%); (4) has a lower content of labile compounds determined by Fourier transform ion cyclotron resonance mass spectrometry (maximum molecular lability boundary: 21% vs. 31%); and (5) has a higher proportion of refractory carboxylic‐rich alicyclic molecules (57% ± 0.5% vs. 51% ± 0.7%) over incubations. Our results emphasize that eutrophication‐triggered coastal dinoflagellate succession has a significant potential for positive feedback to carbon sequestration through the formation of refractory DOC.

Uncovering horizontal and vertical inequities of individual accessibility using mobile phone data - Jinmeng Zhang; Bi Yu Chen; Chenxi Fu; Zehao Yuan; Donggen Wang (Transportation Research Part D: Transport and Environment, 2025)

Sources and fate of nitrate in the unsaturated zone in an alluvial-lacustrine plain - Yuqin Wang; Guangcai Wang; Fu Liao; Erping Bi; Hairu Mao; Zhiyuan Qiao; Hanxiao Wang; Minyue Dou; Chenyu Wang; Xujuan Huang (Journal of Hazardous Materials, 2025)

Designing advanced high-entropy alloy sensors for sensitive low-temperature acetone detection - Boyan Fu; Leyao Bi; Jiahui Lin; Junsheng Wen; Jiaxing Fu; Binglin Zou; Chunjie Wang; Yue Wang (Journal of Environmental Chemical Engineering, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Bayesian-based analysis of sequence activity characteristics in the Bohai Rim region - Jin-Meng Bi; Cheng Song; Fu-Yang Cao (Applied Geophysics, 2025)

Large-scale interviews and plot-based data reveal declining yields of the prized matsutake mushrooms in the major producing areas of China - Yingfeng Bi; Bin Liu; Guangli Chen; Ti Bu; Pengwan Zhang; Qinghong Zhou; Liqin Mu; Yao Fu; Yinxian Shi; Xuefei Yang; Deli Zhai (Journal of Environmental Management, 2025)

Mechanistic insights into carbon black-activated AKT/TMEM175 cascade impairing macrophage-epithelial cross-talk and airway epithelial proliferation - Yawen Feng; Xiaowen Tang; Hongying Fu; Xiaobo Fan; Juntong Wei; Jianying Liu; Hongmei Wang; Huanhuan Bi; Ziyan Chen; Xiaoran Wei; Yuxin Zheng (Environmental Pollution, 2025)

Biogenic iron mineral formation and the fate of arsenic driven by its coupling with ferrous iron in acid mine drainage environment - Shaozu Xu; Mulin Guo; Caihong Jin; Lixiang Zhou; Jing Shi; Peng Fu; Wenlong Bi; Fenwu Liu (Journal of Hazardous Materials, 2025)

Enhanced remediation of cadmium-contaminated farmland by smooth vetch (Vicia villosa var.) coupled with phosphorus/sulfur co-doped biochar: Synergetic performance and mechanism - Fuxuan Bi; Zhao Jiang; Mengning Wang; Qiutong Lin; Xiaoyang Liu; Libo Fu; Hongli Fan; Weidong Cao; Jianhua Qu; Ying Zhang (Journal of Cleaner Production, 2025)

Twin deformable point convolutions for airborne laser scanning point cloud classification - Yong-Qiang Mao; Hanbo Bi; Xuexue Li; Kaiqiang Chen; Zhirui Wang; Xian Sun; Kun Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Multi-performance coupled optimization drives low-carbon retrofitting of site museums - Shanshan Yao; Shugang Yu; Hu Cao; Wenbei Bi; Jiamin Zhang; Duo Zhang; Jingpeng Fu; Pingan Ni (Building and Environment, 2025)

Spatial distribution of bacteria in response to phytoplankton community and multiple environmental factors in surface waters in Sanggou Bay - Song Peng; Rong Bi; Jiwen Liu; Jiaxuan Cui; Xinkai Fu; Xiaotong Xiao; Ruihuan Li; Zengjie Jiang; Shulan Xu; Chuanli Zhang; Xiao-Hua Zhang; Meixun Zhao (Marine Environmental Research, 2025)

Formation of key aroma compounds in Agrocybe aegerita during hot air drying: Amino acids and reducing sugars identified as flavor precursors - Fan Yang; Erbao Chen; Anzhen Fu; Ye Liu; Shuang Bi (Food Chemistry, 2025)

Hot syngas cleanup for pilot two-stage fluidized bed steam-oxygen biomass gasification plant - Zhijie Fu; Nazanin Charchi Aghdam; Sahand Nekoeian; Jing He; Long Cheng; Shida Liu; Lei Zhang; Junnan Chao; Xiaoyang Wei; Ruixu Wang; Bhavya Nagda; Yumeng Zhang; et al. (Bioresource Technology, 2025)

Mechanism of selenium-enriched Bacillus subtilis alleviating perfluorohexanoic acid toxicity in Carassius auratus through the microbiota–gut–brain axis - Xue Jiao; Faye Zhang; Lei Guo; Zheng-Yao Guo; Qiu-Shuang Fu; Cheng-Cheng Bi; Xian-Wei Hou; Ning Wang; Jing-Xiang Zhou; Yue-Hong Li (Aquaculture, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Effect of biochar on anaerobic co-digestion performance of cellulosic ethanol refinery waste liquor with swine manure - Haoran Li; Sunqiang Xu; Yingyan Liang; Can Fu; Yongxin Pang; Zhantian Tang; Guican Bi; Jun Xie (Journal of Water Process Engineering, 2025)

Sequential oxidation procedures with KMnO4: Component characteristics of labile reducing capacity fractions in anaerobic sediments - Xuemei Chen; Zhijun Li; Songjie Fu; Lanwei Liang; Xiaohan Liu; Fang Hu; Wen Zhang; Yonghong Bi; Yang Jiao; Sen Gu; Qingman Li (Science of The Total Environment, 2024)

Effect of different food matrices on the bioaccessibility of vitamin D3 in beverage systems: Comparison between juice and liquid milk - Shaojie Fu; Jinfeng Bi; Xiyu Jiang; Meng Liu; Xuan Liu (Food Chemistry, 2024)

A bounding surface model of methane hydrate-bearing carbonate sand-silt mixtures - Lu Ma; Yuzhe Ren; Jincheng Ren; Shan Chang; Xuemin Zhu; Kaiyu Fu; Huan Ye; Bi Sun (Marine Georesources & Geotechnology, 2024)

Exploring the glycoprotein washing fluid-assisted cleanup for the restoration of oil-contaminated shorelines with environmental integrity - Jiyao Sui; Rengyu Yue; Huifang Bi; Haiyan Fu; Aili Yang; Meng Wang; Chunjiang An (Science of The Total Environment, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Phosphorus dynamics in volcanic soils of Weizhou Island, China: implications for environmental and agricultural applications - Ran Bi; Wei Fu; Xuanni Fu (Environmental Geochemistry and Health, 2024)

Cosmogenic radionuclide Beryllium-7 and Beryllium-10 characteristics and influencing factors in different natural climate regions, China - Xuke Liu; Yunchong Fu; Li Zhang; Yanting Bi; Yuda Cui; Guoqing Zhao (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Quantification- and structural-taste intensity of umami peptides from Agrocybe aegerita through quantitative structure-activity relationship - Fan Yang; Hongyan Meng; Anzhen Fu; Ye Liu; Shuang Bi (Food Chemistry, 2024)

Intensified O2 activation and lattice O supply at inverse oxide-metal interface for catalytic oxidation reactions: A case study in alcohol oxidation - Kun Liu; Yongbin Sun; Jiaqi Si; Cong Fu; Yushui Bi; Xiaomin Zhao; Guofeng Zhao (Chemical Engineering Journal, 2024)

Enhancing total nitrogen removal in constructed wetlands: A Comparative study of iron ore and biochar amendments - Yucui Bi; Fuxing Liu; Zishi Fu; Hongxia Qiao; Junli Wang (Journal of Environmental Management, 2024)

Advances in the delivery and application of antimicrobial peptide-based nanomaterials - Haoran Deng; Shaohua Zhang; Yanxue Fu; Na Dong; Chongpeng Bi; Anshan Shan; Changxuan Shao (Chemical Engineering Journal, 2024)

Physiological and behavioral responses to social isolation and starvation in a social fish - Dan-Dan Xu; Chun-Hua Wang; Jin-Qiu Bi; Huan Luo; Shi-Jian Fu; Bin Li; Ling-Qing Zeng (Applied Animal Behaviour Science, 2024)

Full-waveform hyperspectral LiDAR data decomposition via ranking central locations of natural target echoes (Rclonte) at different wavelengths - Jie Bai; Zheng Niu; Yanru Huang; Kaiyi Bi; Yuwen Fu; Shuai Gao; Mingquan Wu; Li Wang (Remote Sensing of Environment, 2024)

A new species of Eirictis (Mammalia, Carnivora, Mustelidae) from Lower Pleistocene of Yuanmou Basin, Yunnan, China - Arya Farjand; Li-Ya Fu; Qi-Gao Jiangzuo; Zhi-Heng Liu; Jian Wang; Xin-Ying Zhou; Shun-Dong Bi; Li-Hua Wang (Palaeoworld, 2024)

Evaluation of potential prebiotic activity of a novel fucose-containing trisaccharide prepared from bacterial exopolysaccharides - Mengshi Xiao; Jiayuan Bi; Xinmiao Ren; Xiaodan Fu; Dongyu Li; Rong Li; Haijin Mou (Food Bioscience, 2024)

Occurrence, distribution, and ecological risk assessment of pharmaceuticals and personal care products in the surface water of Lipu River, China - Yanan Zhang; Guibin Huang; Qin Zhang; Xiaoqian Bi; Hang Chu; Zixuan Liu; Jun Luo; Shaoyuan Bai; Shengpeng Mo; Hui Wang; Mingming Fu (Environmental Research, 2024)

Fog/cloud processing of atmospheric aerosols from a single particle perspective: A review of field observations - Guohua Zhang; Xiaocong Peng; Wei Sun; Yuzhen Fu; Yuxiang Yang; Dantong Liu; Zongbo Shi; Mingjin Tang; Xinming Wang; Xinhui Bi (Atmospheric Environment, 2024)

The linkage between wintertime sea ice drift and atmospheric circulation in an Arctic ice-ocean coupled simulation - Xi Liang; Haibo Bi; Chengyan Liu; Xichen Li; Dakui Wang; Fu Zhao; Zhongxiang Tian; Ming Li; Na Liu (Ocean Modelling, 2024)

Preparation, structural characterization and rheological properties of a novel fucose-containing exopolysaccharide from Clavibacter michiganensis - Mengshi Xiao; Luying Tang; Xiaodan Fu; Xinmiao Ren; Jiayuan Bi; Jia Wang; Dongyu Li; Qing Kong; Haijin Mou; Changliang Zhu (Food Hydrocolloids, 2024)

Epoxy resin/ aluminium hydroxide/expanded graphite synergistic effects on advancing flame retardancy, mechanical structure and thermal management of octadecanoic acid and octadecanol-based eutectic phase change materials - Hamir Johan Mombeki Pea; Zhoujian An; Xiaoze Du; Bi'an Fu; Dong Zhang; Xiaozheng Wang (Chemical Engineering Journal, 2024)

Wide-bandgap donor polymers from organic photovoltaics as dopant-free hole transport layers for perovskite solar cells - Hongtao Lai; Xin Yang; Liujiang Zhang; Leyu Bi; Binqiang Tian; Huanhuan Wang; Xingyu Gao; Lingfeng Lu; Bin Kan; Xiaofei Ji; Qiang Fu (Chemical Engineering Journal, 2024)

Linking rhizospheric microbiota and metabolite interactions with harvested aboveground carbon and soil carbon of lakeshore reed wetlands in a subtropical region - Junli Wang; Zishi Fu; Hongxia Qiao; Fuxing Liu; Yucui Bi (Plant and Soil, 2024)

Zygotic quiescence prolongs the reproductive cycle in Berchemia sinica (Rhamnaceae) - Fang Ma; Yaolei Fu; Wenjun Wei; Ziwei Li; Jing Liu; Baoxia Bi; Wenzhe Liu (Flora, 2024)

Development of SV2A Ligands for Epilepsy Treatment: A Review of Levetiracetam, Brivaracetam, and Padsevonil - Peng-Peng Wu; Bi-Rong Cao; Fu-Yun Tian; Zhao-Bing Gao (Neuroscience Bulletin, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Non-volatile taste active compounds and umami evaluation of Agrocybe aegerita hydrolysates derived using different enzymes - Fan Yang; Anzhen Fu; Hongyan Meng; Ye Liu; Shuang Bi (Food Bioscience, 2024)

Microwave co-pyrolysis of industrial sludge and waste biomass: Product valorization and synergistic mechanisms - Yang Liu; Asif Ali Siyal; Chunbao Zhou; Chenglong Liu; Jie Fu; Yingwen Zhang; Bang Yao; Li Chao; Huimin Yun; Jianjun Dai; Xiaotao Bi (Chemical Engineering Journal, 2024)

Rapid change of vegetation cover in the Huanghe (Yellow River) mouth wetland and its biogeomorphological feedbacks - Qi Ba; Baoduo Wang; Libin Zhu; Zuomin Fu; Xiao Wu; Houjie Wang; Naishuang Bi (CATENA, 2024)

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

Enhancement of ester biosynthesis in blueberry wines through co-fermentation via cell–cell contact between Torulaspora delbrueckii and Saccharomyces cerevisiae - Yu Wang; Yu Fu; Qi Zhang; Yue Zhu; Qin Yang; Chen Bian; Lu-Lu Zhao; Qi Chen; Hai-Jun Bi; Xiao-Hui Yang; Xue-Ling Gao (Food Research International, 2024)

Genomic and epigenetic characterization of the arsenic-induced oncogenic microRNA-21 - Haoyan Ji; Zhuoyue Bi; Aashna S. Pawar; Akimasa Seno; Bandar Saeed Almutairy; Yao Fu; Yiran Qiu; Wenxuan Zhang; Ziwei Wang; Chitra Thakur; Hongjuan Cui; Liqun Yang; et al. (Environmental Pollution, 2024)

Mixing state and influence factors controlling diurnal variation of particulate nitrophenol compounds at a suburban area in northern China - Ziyong Guo; Xiaodong Hu; Wei Sun; Xiaocong Peng; Yuzhen Fu; Kun Liu; Fengxian Liu; He Meng; Yujiao Zhu; Guohua Zhang; Xinfeng Wang; Likun Xue; et al. (Environmental Pollution, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Microplastics as potential barriers to ultraviolet light emitting diode inactivation of MS2 bacteriophage: Influence of water-quality parameters - Jiuming Hu; Zhiyong Zhang; Xiaoxue Li; Xiaochao Bi; Hongyang Jiang; Wenjie Sun; Ming-Lai Fu; Baoling Yuan (Science of The Total Environment, 2024)

Evaluation of energy-environmental-economic benefits of CNG taxi policy using multi-task deep-learning-based microscopic models and big trajectory data - Bi Yu Chen; Qi Liu; Weishu Gong; Jia Tao; Hui-Ping Chen; Fu-Rong Shi (Travel Behaviour and Society, 2024)

Comparative microwave catalytic pyrolysis of cellulose and lignin in nitrogen and carbon dioxide atmospheres - Yang Liu; Chunbao Zhou; Asif Ali Siyal; Chenglong Liu; Yingwen Zhang; Jie Fu; Huimin Yun; Jianjun Dai; Xiaotao Bi (Journal of Cleaner Production, 2024)

Dimensionally-controlled interlayer spaces of covalent organic frameworks for the oxygen evolution reaction - Minghao Liu; Yubin Fu; Shuai Bi; Shuai Yang; Xiubei Yang; Xuewen Li; George Zheng Chen; Jun He; Qing Xu; Gaofeng Zeng (Chemical Engineering Journal, 2024)

Tumor suppressive activity of AHR in environmental arsenic-induced carcinogenesis - Ziwei Wang; Yao Fu; Akimasa Seno; Zhuoyue Bi; Aashna S. Pawar; Haoyan Ji; Bandar Saeed Almutairy; Yiran Qiu; Wenxuan Zhang; Chitra Thakur; Fei Chen (Toxicology and Applied Pharmacology, 2023)

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

Significantly improved high-temperature capacitive performance in polymer dielectrics utilizing ultra-small carbon quantum dots with Coulomb-blockade effect - Hangchuan Cai; Rui Wang; Bin Gou; Jing Fu; Yujie Zhu; Hao Yang; Jiangang Zhou; Manxi Li; An Zhong; Daoming Zhang; Huasong Xu; Chunhui Bi; et al. (Chemical Engineering Journal, 2023)

Impact of extended dryland crop rotation on sustained potato cultivation in Northwestern China - Yuhui Liu; Zhitao Li; Yuanming Li; Zhen Liu; Fu Chen; Zhenzhen Bi; Chao Sun; Caimei Tang; Panfeng Yao; Anming Yuan; Junlian Zhang; Yantai Gan; et al. (Resources, Conservation and Recycling, 2023)

Interfacial mechanism and inactivation efficiency of bacteriophage MS2 by ozone in high turbidity and algal-laden water resource - Lu Wang; Yi-bo Hu; Xiaochao Bi; V. Vasanthakumar; Zhiyong Zhang; Ming-Lai Fu; Wenjie Sun; Baoling Yuan (Journal of Water Process Engineering, 2023)

Nanofiltration membrane with asymmetric polyamide dual-layer through interfacial polymerization for enhanced separation performance - Xinyu Fu; Jianqiang Wang; Yingyao He; Yanli Ji; Qiuyan Bi; Xiao Wang; Fu Liu (Desalination, 2023)

Highly efficient production of monocyclic aromatics from catalytic co-pyrolysis of biomass and plastic with nitrogen-doped activated carbon catalyst - Xiaona Lin; Xiaoyun Chen; Peng Fu; Binbin Tang; Dongmei Bi (Chemical Engineering Journal, 2023)

Advanced low-strength wastewater treatment, side-stream phosphorus recovery, and in situ sludge reduction with aerobic granular sludge - Qiulai He; Xiaohui Yan; Zhiyi Xie; Peng Xu; Zhidong Fu; Jinfeng Li; Liang Liu; Peng Bi; Baokun Xu; Jingwei Ma (Bioresource Technology, 2023)

Efficient photodegradation of micropollutants by tubular carbon nitride: The role of nitrogen defects - Lanbo Bi; Jimin Shen; Pengwei Yan; Gang Fu; Jiaxu Zhang; Jing Kang; Binyuan Wang; Linghan Li; Yanchi Zhou; Zhonglin Chen (Journal of Cleaner Production, 2023)

Performance of anaerobic/oxic/anoxic simultaneous nitrification, denitrification and phosphorus removal system overwhelmingly dominated by Candidatus_Competibacter: Effect of aeration time - Jingwei Ma; Yaning Ji; Zhidong Fu; Xiaohui Yan; Peng Xu; Jinfeng Li; Liang Liu; Peng Bi; Liang Zhu; Baokun Xu; Qiulai He (Bioresource Technology, 2023)

Comparative transcriptome analysis of grafting to improve chilling tolerance of cucumber - Xin Fu; Chun-Yu Lv; Yan-Yan Zhang; Xi-Zhen Ai; Huan-Gai Bi (Protoplasma, 2023)

Seismicity characteristics of secondary faults in the Zhangjiakou-Bohai tectonic zone - Jin-Meng Bi; Fu-Yang Cao; Ling-Qin Meng (Applied Geophysics, 2023)

Effects of substrate improvement on winter nitrogen removal in riparian reed (Phragmites australis) wetlands: rhizospheric crosstalk between plants and microbes - Junli Wang; Zishi Fu; Fuxing Liu; Hongxia Qiao; Yucui Bi (Environmental Science and Pollution Research, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Molecular characteristics, sources and transformation of water-insoluble organic matter in cloud water - Wei Sun; Ziyong Guo; Xiaocong Peng; Juying Lin; Yuzhen Fu; Yuxiang Yang; Guohua Zhang; Bin Jiang; Yuhong Liao; Duohong Chen; Xinming Wang; Xinhui Bi (Environmental Pollution, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Organophosphate tri- and diesters in source water supply and drinking water treatment systems of a metropolitan city in China - Xiaolan Zhang; Yuhao Bi; Minghui Fu; Xinyu Zhang; Bingli Lei; Xin Huang; Zhenzhen Zhao (Environmental Geochemistry and Health, 2023)

In-cloud scavenging of chemically segregated particle types by individual particle observation - Yuxiang Yang; Xiaocong Peng; Guohua Zhang; Xiaodong Hu; Ziyong Guo; Wei Sun; Yuzhen Fu; Feng Jiang; Jie Ou; Xiang Ding; Xinming Wang; Xinhui Bi (Applied Geochemistry, 2023)

An ultra-compact acoustofluidic device based on the narrow-path travelling surface acoustic wave (np-TSAW) for label-free isolation of living circulating tumor cells - Wenping Geng; Yukai Liu; Nanxin Yu; Xiaojun Qiao; Miaomiao Ji; Yaokai Niu; Liya Niu; Wenxiao Fu; Huiyi Zhang; Kaixi Bi; Xiujian Chou (Analytica Chimica Acta, 2023)

Underwater ejection multifield coupling model and response characteristics - Haotian Liu; Shangming Li; Debin Fu; Fengyang Bi (Ocean Engineering, 2023)

Numerical analysis of steady-state mechanical characteristics of the flexible spoke non-pneumatic tire under multiple working conditions - Laiyun Ku; Hongxun Fu; Kai Chen; Jinyan Zhang; Senyu Bi; Lei Zhou (Journal of Terramechanics, 2023)

Efficient removal of doxycycline using Schwertmannite as a heterogeneous Fenton-like catalyst over a wide pH range - Yu Tian; Fenwu Liu; Bo Sun; Zhenye Tong; Peng Fu; Jingzhi Zhang; Wenlong Bi; Shaozu Xu; Guangpeng Pei (Journal of Environmental Chemical Engineering, 2023)

Ice nucleation activity of airborne pollen: A short review of results from laboratory experiments - Peimin Duan; Wei Hu; Zhijun Wu; Kai Bi; Jialei Zhu; Pingqing Fu (Atmospheric Research, 2023)

Activity characteristics of significant earthquake swarms in the Bohai Rim region - Jin-Meng Bi; Cheng Song; Fu-Yang Cao (Applied Geophysics, 2023)

Molecular characteristics and compositions affecting light absorption features of cloud water revealed by Fourier transform ion cyclotron resonance mass spectrometry - Ziyong Guo; Wei Sun; Xiaodong Hu; Juying Lin; Yuzhen Fu; Xiaocong Peng; Bin Jiang; Yuhong Liao; Guohua Zhang; Xinming Wang; Ping'an Peng; Xinhui Bi (Atmospheric Environment, 2023)

Shape-controlled synthesis of Pd nanotetrahedrons with Pt-doped surfaces for highly efficient electrocatalytic oxygen reduction and formic acid oxidation - Liuxuan Luo; Zehao Tan; Cehuang Fu; Rui Xue; Xiaojing Cheng; Tianzi Bi; Lutian Zhao; Yangge Guo; Xiyang Cai; Jiewei Yin; Shuiyun Shen; Junliang Zhang (Chemical Engineering Journal, 2023)

Corrigendum to “Rapid start-up and stable operation of an aerobic/oxic/anoxic simultaneous nitrification, denitrification, and phosphorus removal reactor with no sludge discharge” [Bioresour. Technol. 362 (2022) 127777] - Qiulai He; Xiaohui Yan; Zhidong Fu; Yihang Zhang; Peng Bi; Xingliang Mo; Peng Xu; Jingwei Ma (Bioresource Technology, 2023)

Effect of particulate matters on inactivation of bacteriophage MS2 under irradiation above 320 nm - Xiaoxue Li; Xiaochao Bi; Xiaoyang Shi; La Rao; Ming-Lai Fu; Wenjie Sun; Baoling Yuan (Environmental Science and Pollution Research, 2022)

Tea consumption and cerebral hemorrhage risk: a meta-analysis - Pengfei Cheng; Junxiang Zhang; Wenting Liu; Quan Sun; Zhaoxin Fu; Hao Lin; Sheng Bi; Jiaying Zhu (Acta Neurologica Belgica, 2022)

Effects of ecological restoration on soil biogenic elements and their ecological stoichiometry in the Yellow River Delta, China - Dongxue Li; Yi’na Li; Yiliang Xie; Baoshan Cui; Zhonghua Ning; Shuyan Zhang; Zhenggang Bi; Shouqiang Fu; Chunguang Che (Frontiers in Marine Science, 2022)
Coastal wetlands serve as sources and sinks of carbon, nitrogen, phosphorus, and sulfur, and their ecological stoichiometry intuitively indicates the biogeochemical cycle process of the region. This study investigated the changing trend of the contents of soil organic carbon (i.e., SOC), total nitrogen (i.e., TN), total phosphorus (i.e., TP), and total sulfur (i.e., TS) and their ecological stoichiometric ratios in 2019-2021 in the Yellow River Delta (including north and south banks) under the Internationally Important Wetland Biodiversity Conservation Project by conducting field surveys and experiments. The results showed that SOC, TN, and TP showed the highest content in the North Unrestoration, while the TS content appeared highest in the North Restoration. In addition, ecological restoration improved the biogenic element stability in both banks and improved the stability of ecological stoichiometry on the north bank while decreasing the ecological stoichiometry stability on the south bank. Notably, the changing trend of soil C/S in the North Unrestoration exhibited a considerably different profile similarity from the North Restoration, which indicates that the ecological restoration changed the wetland ecosystem from the perspective of soil C/S. Furthermore, the high content of soil biogenic elements SOC and high ratio of soil ecological stoichiometry C/N and C/S in the Yellow River Delta induce that they are more sensitive to environmental change. Over the three years, the contributions of soil moisture content, soil salinity, and pH to soil biogenic element contents and their stoichiometric ratios were 32.20%, 49.30%, and 18.50% on the north bank, respectively, and 85.70%, 8.50%, and 5.80% on the south bank, respectively. This study implies that ecological restoration generally has a positive effect on the soil biogenic element contents and their ecological stoichiometry in the Yellow River Delta and provides a reference for delta restoration.

Failure Mechanism and Control of Surrounding Rock of Mining Roadway Under Overlying Goaf - Jiyuan Yang; Junliang Dong; Kun Lv; Zhongwei Bi; Xingyu Fu; Bin Zhao (Geotechnical and Geological Engineering, 2022)

Field investigation and numerical simulation on rockfalls in Zhangmu Town, Tibet, China - Zhong-fu Wang; Han-dong Liu; Si-ming He; Dan Bi (Journal of Mountain Science, 2022)

Optimal array layout of cylindrical baffles to reduce energy of rock avalanche - Yu-zhang Bi; Dong-po Wang; Xian-lei Fu; Yi-xiong Lin; Xin-po Sun; Zhe-yuan Jiang (Journal of Mountain Science, 2022)

The exploration of Parkinson’s disease: a multi-modal data analysis of resting functional magnetic resonance imaging and gene data - Xia-an Bi; Hao Wu; Yiming Xie; Lixia Zhang; Xun Luo; Yu Fu (Brain Imaging and Behavior, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Seasonal variation of nitrogen biogeochemical processes constrained by nitrate dual isotopes in cascade reservoirs, Southwestern China - Sai-Nan Chen; Fu-Jun Yue; Xiao-Long Liu; Jun Zhong; Yuan-Bi Yi; Wan-Fa Wang; Yulin Qi; Hua-Yun Xiao; Si-Liang Li (Environmental Science and Pollution Research, 2021)

Spatiotemporal characteristics of sea ice transport in the Baffin Bay and its association with atmospheric variability - Weifu Sun; Haibo Bi; Min Fu; Xi Liang; Yunhe Wang; Yu Liang; Jue Huang; Haijun Huang; Liwen Yan; Qinglong Yu; Shuang Liang (Acta Oceanologica Sinica, 2021)

The Role of Reward System in Dishonest Behavior: A Functional Near-Infrared Spectroscopy Study - Yibiao Liang; Genyue Fu; Runxin Yu; Yue Bi; Xiao Pan Ding (Brain Topography, 2021)

Patterns of mitochondrial DNA fragmentation in bread wheat (Triticum aestivum L.) seeds under ex situ genebank storage and artificial aging - Yong-Bi Fu; Zaheer Ahmed; Hui Yang; Carolee Horbach; Gregory W. Peterson (Genetic Resources and Crop Evolution, 2020)

Hydrogen sulfide is required for salicylic acid–induced chilling tolerance of cucumber seedlings - Dong-Yun Pan; Xin Fu; Xiao-Wei Zhang; Feng-Jiao Liu; Huan-Gai Bi; Xi-Zhen Ai (Protoplasma, 2020)

Auxin acts as a downstream signaling molecule involved in hydrogen sulfide-induced chilling tolerance in cucumber - Xiao-Wei Zhang; Feng-Jiao Liu; Jiang Zhai; Fu-De Li; Huan-Gai Bi; Xi-Zhen Ai (Planta, 2020)

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

The Inhibitory Effects of Nitrogen Deposition on Asymbiotic Nitrogen Fixation are Divergent Between a Tropical and a Temperate Forest - Mianhai Zheng; Wei Zhang; Yiqi Luo; Shiqiang Wan; Shenglei Fu; Senhao Wang; Nan Liu; Qing Ye; Junhua Yan; Bi Zou; Chengliang Fang; Yuxi Ju; et al. (Ecosystems, 2019)

Two new noroleanane-type triterpenoid saponins from the stems of Stauntonia chinensis - Tong-Tong Feng; Hui-Zheng Fu; Yi-Sheng Yang; Zhi-Qiang Zhou; Mian Dai; Hong-Yu Bi; Dong Wang (Natural Product Research, 2019)

Satellite-observed trends in the Arctic sea ice concentration for the period 1979–2016 - Yunhe Wang; Haibo Bi; Haijun Huang; Yanxia Liu; Yilin Liu; Xi Liang; Min Fu; Zehua Zhang (Journal of Oceanology and Limnology, 2019)

Genotyping-by-sequencing empowered genetic diversity analysis of Jordanian oat wild relative Avena sterilis - Nawal Al-Hajaj; Gregory W. Peterson; Carolee Horbach; Khaled Al-Shamaa; Nicholas A. Tinker; Yong-Bi Fu (Genetic Resources and Crop Evolution, 2018)

The Observation of Ice-Nucleating Particles Active at Temperatures above–15°C and Its Implication on Ice Formation in Clouds - Kai Bi; Xincheng Ma; Yunbo Chen; Shizuo Fu; Huiwen Xue (Journal of Meteorological Research, 2018)

Recent satellite-derived sea ice volume flux through the Fram Strait: 2011–2015 - Haibo Bi; Yunhe Wang; Wenfeng Zhang; Zehua Zhang; Yu Liang; Yi Zhang; Wenmin Hu; Min Fu; Haijun Huang (Acta Oceanologica Sinica, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Genome re‐sequencing and simple sequence repeat markers reveal the existence of divergent lineages in the Canadian Puccinia striiformis f. sp. tritici population with extensive DNA methylation - Gurcharn S. Brar; Sajid Ali; Dinah Qutob; Stephen Ambrose; Kun Lou; Ron Maclachlan; Curtis J. Pozniak; Yong‐Bi Fu; Andrew G. Sharpe; Hadley R. Kutcher (Environmental Microbiology, 2018)
Summary Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is an important disease in Canada. The worldwide genetic structure of Pst populations have been characterized, excluding Canada. Here, we elucidated the genetic structure of the western Canadian Pst population using molecular markers, revealing the presence of four divergent lineages with predominantly clonal structure. In the worldwide context, two previously reported lineages were identified: PstS0 (22%), representing an old Northwestern‐European and PstS1 (35%), an invasive warm‐temperature adapted. Additionally, two new, unreported lineages, PstPr (9%) and PstS1 ‐related (35%), were detected, which produced more telia than other lineages and had double the number of unique recombination events. The PstPr was a recent invasion, and likely evolved in a diverse, recombinant population as it was closely related to the PstS5 , PstS7 /Warrior, PstS8 /Kranich, and PstS9 lineages originating from sexually recombining populations in the centre of diversity. The DNA methylation analysis revealed DNA‐methyltransferase1‐homologs, providing compelling evidence for epigenetic regulation and as a first report, an average of ∼5%, 5hmC in the Puccinia epigenome merits further investigation. The divergent lineages in the Canadian Pst population with the potential for genetic recombination, as well as epigenetic regulation needs consideration in the context of pathogen adaptation and management.

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Increasing winter conductive heat transfer in the Arctic sea-ice-covered areas: 1979–2014 - Xieyu Fan; Haibo Bi; Yunhe Wang; Min Fu; Xuan Zhou; Xiuli Xu; Haijun Huang (Journal of Ocean University of China, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

An R version of FPTest for testing differences in allelic count - Mo-Hua Yang; Yong-Bi Fu (Conservation Genetics Resources, 2017)

Erratum to: The Rho kinase inhibitor, fasudil, ameliorates diabetes-induced cardiac dysfunction by improving calcium clearance and actin remodeling - Dongwu Lai; Jing Gao; Xukun Bi; Hong He; Xiaolu Shi; Shaoxiang Weng; Yu Chen; Ying Yang; Yang Ye; Guosheng Fu (Journal of Molecular Medicine, 2017)

The Rho kinase inhibitor, fasudil, ameliorates diabetes-induced cardiac dysfunction by improving calcium clearance and actin remodeling - Dongwu Lai; Jing Gao; Xukun Bi; Hong He; Xiaolu Shi; Shaoxiang Weng; Yu Chen; Ying Yang; Yang Ye; Guosheng Fu (Journal of Molecular Medicine, 2017)

Patterns of SSR variation in bread wheat (Triticum aestivum L.) seeds under ex situ genebank storage and accelerated ageing - Yong-Bi Fu; Mo-Hua Yang; Carolee Horbach; Dallas Kessler; Axel Diederichsen; Frank M. You; Hong Wang (Genetic Resources and Crop Evolution, 2017)

Removal of polybrominated diphenyl ethers by biomass carbon-supported nanoscale zerovalent iron particles: influencing factors, kinetics, and mechanism - Rongbing Fu; Zhen Xu; Lin Peng; Dongsu Bi (Environmental Science and Pollution Research, 2016)

High-density marker profiling confirms ancestral genomes of Avena species and identifies D-genome chromosomes of hexaploid oat - Honghai Yan; Wubishet A. Bekele; Charlene P. Wight; Yuanying Peng; Tim Langdon; Robert G. Latta; Yong-Bi Fu; Axel Diederichsen; Catherine J. Howarth; Eric N. Jellen; Brian Boyle; Yuming Wei; et al. (Theoretical and Applied Genetics, 2016)

Photosynthesis, antioxidant system and gene expression of bermudagrass in response to low temperature and salt stress - Ao Liu; Zhengrong Hu; Aoyue Bi; Jibiao Fan; Margaret Mukami Gitau; Erick Amombo; Liang Chen; Jinmin Fu (Ecotoxicology, 2016)

Arctic sea ice thickness changes in terms of sea ice age - Haibo Bi; Min Fu; Ke Sun; Yilin Liu; Xiuli Xu; Haijun Huang (Acta Oceanologica Sinica, 2016)

Comparison of seemingly unrelated regressions with error-in-variable models for developing a system of nonlinear additive biomass equations - Liyong Fu; Yuancai Lei; Guangxing Wang; Huiquan Bi; Shouzheng Tang; Xinyu Song (Trees, 2016)

Dispersion function of Rayleigh waves in porous layered half-space system - Shou-Guo Yan; Fu-Li Xie; Chang-Zheng Li; Bi-Xing Zhang (Applied Geophysics, 2016)

Long noncoding RNA FGFR3-AS1 promotes osteosarcoma growth through regulating its natural antisense transcript FGFR3 - Jiabing Sun; Xuming Wang; Chunjiang Fu; Xiaoyu Wang; Jilong Zou; Hanbing Hua; Zhenggang Bi (Molecular Biology Reports, 2016)

Measurement of aerosol effective density by single particle mass spectrometry - GuoHua Zhang; XinHui Bi; BingXue Han; Ning Qiu; ShouHui Dai; XinMing Wang; GuoYing Sheng; JiaMo Fu (Science China Earth Sciences, 2016)

Cardioprotective Effect of Anisodamine Against Myocardial Ischemia Injury and its Influence on Cardiomyocytes Apoptosis - Kun Xing; Xianghua Fu; Lingling Jiang; Yanbo Wang; Wei Li; Xinshun Gu; Guozhen Hao; Qing Miao; Xiaolin Ge; Yuhong Peng; Wei Geng; Shiru Bai; et al. (Cell Biochemistry and Biophysics, 2015)

Understanding crop genetic diversity under modern plant breeding - Yong-Bi Fu (Theoretical and Applied Genetics, 2015)

A Crucial Role of IL-17 in Bone Resorption During Rejection of Fresh Bone Xenotransplantation in Rats - Jiabing Sun; Xuming Wang; Chunjiang Fu; Dewei Wang; Zhenggang Bi (Cell Biochemistry and Biophysics, 2015)

Origin of Triassic granites in central Hunan Province, South China: constraints from zircon U–Pb ages and Hf and O isotopes - Shanling Fu; Ruizhong Hu; Xianwu Bi; Youwei Chen; Jiehua Yang; Yong Huang (International Geology Review, 2015)

Thai elite cassava genetic diversity was fortuitously conserved through farming with different sets of varieties - Yong-Bi Fu; Preeya P. Wangsomnuk; Benjawan Ruttawat (Conservation Genetics, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Improvement of pseudo-static method for slope stability analysis - Chang-wei Yang; Jian-jing Zhang; Xiao Fu; Chuan-bin Zhu; Jun-wei Bi (Journal of Mountain Science, 2014)

Genetic diversity analysis of yellow mustard (Sinapis alba L.) germplasm based on genotyping by sequencing - Yong-Bi Fu; Bifang Cheng; Gregory W. Peterson (Genetic Resources and Crop Evolution, 2014)

Contribution of arbuscular mycorrhizal fungi to the development of maize (Zea mays L.) grown in three types of coal mine spoils - Wei Guo; Renxin Zhao; Ruiying Fu; Na Bi; Lixin Wang; Wenjing Zhao; Jiangyuan Guo; Jun Zhang (Environmental Science and Pollution Research, 2014)

Research on the imaging of concrete defect based on the pulse compression technique - Chang-Zheng Li; Bi-Xing Zhang; Fang-Fang Shi; Fu-Li Xie (Applied Geophysics, 2013)

Geology, mineralization, and geochronology of the Qianhe gold deposit, Xiong’ershan area, southern North China Craton - Ke-Fei Tang; Jian-Wei Li; David Selby; Mei-Fu Zhou; Shi-Jian Bi; Xiao-Dong Deng (Mineralium Deposita, 2013)

Characterization and evolutionary analysis of Brassica species-diverged sequences containing simple repeat units - Lijuan Wei; Meili Xiao; Annaliese S. Mason; Bi Ma; Kun Lu; Jiana Li; Link Katrin; Donghui Fu (Genes & Genomics, 2013)

Seedling growth and soil nutrient availability in exotic and native tree species: implications for afforestation in southern China - Faming Wang; Weixing Zhu; Bi Zou; Deborah A. Neher; Shenglei Fu; Hanping Xia; Zhian Li (Plant and Soil, 2013)

Characteristics, loss and gain of atmospheric carbonyl compounds in winters of 2008–2010 in Pearl River Delta region, China - Yonglin Liu; Xinhui Bi; L. Y. Chan; Sheng Wen; Xinming Wang; Guoying Sheng; Jiamo Fu (Journal of Atmospheric Chemistry, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Catechol-O-methyltransferase (COMT) Val158Met polymorphism and risk of osteoporotic fracture - Yang Cao; Dawei Wang; Bin Liu; Guijun Yao; Yutuo Fu; Zhenggang Bi (Molecular Biology Reports, 2012)

Variation in phenotypic characters of pale flax (Linum bienne Mill.) from Turkey - Hüseyin Uysal; Orhan Kurt; Yong-Bi Fu; Axel Diederichsen; Peter Kusters (Genetic Resources and Crop Evolution, 2012)

Gold distribution in As-deficient pyrite and telluride mineralogy of the Yangzhaiyu gold deposit, Xiaoqinling district, southern North China craton - Shi-Jian Bi; Jian-Wei Li; Mei-Fu Zhou; Zhan-Ke Li (Mineralium Deposita, 2011)

Genetic evidence for early flax domestication with capsular dehiscence - Yong-Bi Fu (Genetic Resources and Crop Evolution, 2011)

Genetic Diversity of Kenyan Potato Germplasm Revealed by Simple Sequence Repeat Markers - Charles Lung’aho; George N. Chemining’wa; Yong-Bi Fu; Solomon I. Shibairo; Margaret J. Hutchinson; Humberto G. Paniagua (American Journal of Potato Research, 2011)

Silencing of HMGA1 expression by RNA interference suppresses growth of osteogenic sarcoma - Shaohui Yuan; Qi Pan; ChunJiang Fu; ZhengGang Bi (Molecular and Cellular Biochemistry, 2011)

Clinical significance of miR-221 and its inverse correlation with p27Kip1 in hepatocellular carcinoma - Xinhui Fu; Qian Wang; Jingsong Chen; Xiaohui Huang; Xilin Chen; Liangqi Cao; Haoxiang Tan; Wen Li; Longjuan Zhang; Jiong Bi; Qiao Su; Lianzhou Chen (Molecular Biology Reports, 2011)

Allelic changes in bread wheat cultivars were associated with long-term wheat trait improvements - Yong-Bi Fu; Daryl J. Somers (Euphytica, 2011)

Genetic diversity of cultivated flax (Linum usitatissimum L.) and its wild progenitor pale flax (Linum bienne Mill.) as revealed by ISSR markers - Hüseyin Uysal; Yong-Bi Fu; Orhan Kurt; Gregory W. Peterson; Axel Diederichsen; Peter Kusters (Genetic Resources and Crop Evolution, 2010)

Establishment of a multiplex RT-PCR assay to detect different lineages of swine H1 and H3 influenza A viruses - Guanghua Fu; Mengda Liu; Wenshu Zeng; Juan Pu; Yuhai Bi; Guangpeng Ma; Jinhua Liu (Virus Genes, 2010)

Population-based resequencing analysis of improved wheat germplasm at wheat leaf rust resistance locus Lr21 - Yong-Bi Fu; Gregory W. Peterson; Brent D. McCallum; Li Huang (Theoretical and Applied Genetics, 2010)

Phylogenetic network of Linum species as revealed by non-coding chloroplast DNA sequences - Yong-Bi Fu; Robin G. Allaby (Genetic Resources and Crop Evolution, 2010)

Characterization of microsatellite DNA markers in the Emei moustache toads (Leptobrachium boringii) - Ke Bi; Duncan Deng; M. Kathrine A. Crosby; Jinzhong Fu (Conservation Genetics, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Eleven novel microsatellite markers developed from the living fossil Ginkgo biloba (Ginkgoaceae) - Xiao-Ling Yan; Ye-Ye Chen; Bi-Cai Guan; Cheng-Xin Fu (Conservation Genetics, 2009)

Surface turbulent flux measurements over the Loess Plateau for a semi-arid climate change study - Jinqing Zuo; Jianping Huang; Jiemin Wang; Wu Zhang; Jianrong Bi; Guoyin Wang; Weijing Li; Peijian Fu (Advances in Atmospheric Sciences, 2009)

Frequent mitochondrial gene introgression among high elevation Tibetan megophryid frogs revealed by conflicting gene genealogies - WEI CHEN; KE BI; JINZHONG FU (Molecular Ecology, 2009)
Historical mitochondrial introgression causes differences between a species’ mitochondrial gene genealogy and its nuclear gene genealogy, making tree‐based species delineation ambiguous. Using sequence data from one mitochondrial gene (cytochrome b ) and three nuclear genes (introns), we examined the evolutionary history of four high elevation Tibetan megophryid frog species, Scutiger boulengeri , Scutiger glandulatus , Scutiger mammatus and Scutiger tuberculatus . The three nuclear genes shared a similar history but the mitochondrial gene tree suggested a drastically different evolutionary scenario. The conflicts between them were explained by multiple episodes of mitochondrial introgression events via historical interspecific hybridization. ‘Foreign’ mitochondrial genomes might have been fixed in populations and extended through a large portion of the species’ distribution. Some hybridization events were probably as old as 10 Myr, while others were recent. An F 1 hybrid was also identified. Historical hybridization events among the four species appeared to be persistent and were not restricted to the period of Pleistocene glaciation, as in several other well‐studied cases. Furthermore, hybridization involved several species and occurred in multiple directions, and there was no indication of one mitochondrial genome being superior to others. In addition, incomplete lineage sorting resulting from budding speciation may have also explained some discrepancies between the mitochondrial DNA and nuclear gene trees. Combining all evidences, the former ‘ Scutiger mammatus ’ appeared to be two species, including a new species. With the availability of a wide range of highly variable nuclear gene markers, we recommend using a combination of mitochondrial gene and multiple nuclear genes to reveal a complete species history.

Genetic Diversity of Canadian and Exotic Potato Germplasm Revealed by Simple Sequence Repeat Markers - Yong-Bi Fu; Gregory W. Peterson; Ken W. Richards; T. Richard Tarn; Jane E. Percy (American Journal of Potato Research, 2009)

Consumption of Grape Seed Extract Prevents Amyloid-β Deposition and Attenuates Inflammation in Brain of an Alzheimer’s Disease Mouse - Yan-Jiang Wang; Philip Thomas; Jin-Hua Zhong; Fang-Fang Bi; Shantha Kosaraju; Anthony Pollard; Michael Fenech; Xin-Fu Zhou (Neurotoxicity Research, 2009)

An overview of the Semi-arid Climate and Environment Research Observatory over the Loess Plateau - Jianping Huang; Wu Zhang; Jinqing Zuo; Jianrong Bi; Jinsen Shi; Xin Wang; Zhoulin Chang; Zhongwei Huang; Su Yang; Beidou Zhang; Guoyin Wang; Guanghong Feng; et al. (Advances in Atmospheric Sciences, 2008)

AFLP variation in 25 Avena species - Yong-Bi Fu; David J. Williams (Theoretical and Applied Genetics, 2008)

Distribution, Source Apportionment, and Transport of PAHs in Sediments from the Pearl River Delta and the Northern South China Sea - Xiao-Jun Luo; She-Jun Chen; Bi-Xian Mai; Guo-Ying Sheng; Jia-Mo Fu; Eddy Y. Zeng (Archives of Environmental Contamination and Toxicology, 2008)

Isolation and characterization of microsatellite markers in Dysosma versipellis (Berberidaceae), a rare endemic from China - Bi-Cai Guan; Ying-Xiong Qiu; Cheng-Xin Fu (Conservation Genetics, 2008)

Genealogical relationships of southern Ontario polyploid unisexual salamanders (genus Ambystoma) inferred from intergenomic exchanges and major rDNA cytotypes - Ke Bi; James P. Bogart; Jinzhong Fu (Chromosome Research, 2008)

Genealogical relationships of southern Ontario polyploid unisexual salamanders (genus Ambystoma) inferred from intergenomic exchanges and major rDNA cytotypes - Ke Bi; James P. Bogart; Jinzhong Fu (Chromosome Research, 2008)

Edaravone neuroprotection effected by suppressing the gene expression of the Fas signal pathway following transient focal ischemia in rats - Bo Xiao; Fang -Fang Bi; Yue -Qiang Hu; Fa -Fa Tian; Zhi -Guo Wu; Hadi M. Mujlli; Ling Ding; Xin -Fu Zhou (Neurotoxicity Research, 2007)

Microsatellite variation in Avena sterilis oat germplasm - Yong-Bi Fu; James Chong; Tom Fetch; Ming-Li Wang (Theoretical and Applied Genetics, 2007)

Precise molybdenite Re–Os and mica Ar–Ar dating of the Mesozoic Yaogangxian tungsten deposit, central Nanling district, South China - Jiantang Peng; Mei-Fu Zhou; Ruizhong Hu; Nengping Shen; Shunda Yuan; Xianwu Bi; Andao Du; Wenjun Qu (Mineralium Deposita, 2006)

Genetic Variation and Relationships of Pedigree-Known Oat, Wheat, and Barley Cultivars Releaved by Bulking and Single-Plant Sampling - Yong-Bi Fu; William G. Legge; John M. Clarke; Ken W. Richards (Genetic Resources and Crop Evolution, 2006)

Chemical Composition and Sources of PM10 and PM2.5 Aerosols in Guangzhou, China - Xinhua Wang; Xinhui Bi; Guoying Sheng; Jiamo Fu (Environmental Monitoring and Assessment, 2006)

Seasonal Variation of the Particle Size Distribution of n-Alkanes and Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Aerosol of Guangzhou, China - X. L. Tang; X. H. Bi; G. Y. Sheng; J. H. Tan; J. M. FU (Environmental Monitoring and Assessment, 2006)

Impact of plant breeding on genetic diversity of the Canadian hard red spring wheat germplasm as revealed by EST-derived SSR markers - Yong-Bi Fu; Gregory W. Peterson; Ju-Kyung Yu; Lifeng Gao; Jizeng Jia; Ken W. Richards (Theoretical and Applied Genetics, 2006)

Phenotypic and Molecular (RAPD) Differentiation of Four Infraspecific Groups of Cultivated Flax (Linum usitatissimum L. subsp. usitatissimum) - Axel Diederichsen; Yong-Bi Fu (Genetic Resources and Crop Evolution, 2006)

Evidence of the domestication history of flax (Linum usitatissimum L.) from genetic diversity of the sad2 locus - Robin G. Allaby; Gregory W. Peterson; David Andrew Merriwether; Yong-Bi Fu (Theoretical and Applied Genetics, 2005)

Patterns of AFLP variation in a core subset of cultivated hexaploid oat germplasm - Yong Bi Fu; Gregory W. Peterson; David Williams; Ken W. Richards; Jennifer Mitchell Fetch (Theoretical and Applied Genetics, 2005)

Allelic reduction and genetic shift in the Canadian hard red spring wheat germplasm released from 1845 to 2004 - Yong-Bi Fu; Gregory W. Peterson; Ken W. Richards; Daryl Somers; Ron M. DePauw; John M. Clarke (Theoretical and Applied Genetics, 2005)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Genetic diversity of Pakistan wheat germplasm as revealed by RAPD markers - Iftikhar Ahmad Khan; Faisal Saeed Awan; Aftab Ahmad; Yong-Bi Fu; Ahsan Iqbal (Genetic Resources and Crop Evolution, 2005)

Assessment of bulking strategies for RAPD analyses of flax germplasm - Yong-Bi Fu; Sarah Guerin; Gregory W. Peterson; John E. Carlson; K.W. Richards (Genetic Resources and Crop Evolution, 2003)

RAPD analysis of genetic relationships of seven flax species in the genus Linum L - Yong-Bi Fu; Gregory Peterson; Axel Diederichsen; K.W. Richards (Genetic Resources and Crop Evolution, 2002)

Genetic diversity within a range of cultivars and landraces of flax (Linum usitatissimum L.) as revealed by RAPDs - Yong-Bi Fu; Axel Diederichsen; K.W. Richards; Gregory Peterson (Genetic Resources and Crop Evolution, 2002)

Incomplete Block Designs for Genetic Testing: Statistical Efficiencies with Missing Observations - Yong-Bi Fu; Alvin D. Yanchuk; Gene Namkoong; G. Peter Y. Clarke (Forest Science, 1999)
Missing observations are common in forest genetic field trials and are expected to reduce statistical efficiencies of any applied field designs. Such reductions could lower the presumed efficiency and other benefits of implementing any incomplete block designs (ICBs). In this study, we addressed this by computer simulation of a full-sib progeny trial with up to 20% of the observations missing. Four scenarios of missing observations (random, row, column, and genetic mortality) and tests of both clones and seedling families were examined. Two types of ICBs (alpha and no constraint) with single-tree plots, and their corresponding randomized complete block design (RCB), were considered on test sites with gradient and patchy environmental variation. Our simulations show that: (1) the statistical efficiencies of estimating family (or clone) means with both ICB and RCB were very sensitive to the percentage, not the scenarios, of missing observations examined; (2) the statistical efficiencies for both ICB and RCB were reduced as the number of missing observations increased, except in the cases of clonal genetic mortality; (3) the relative efficiency of ICB over RCB (at equal levels of missing observations) was reduced slightly as the level of missing observations increased; (4) the relative efficiencies for the seedling family tests were a little more sensitive to the levels of missing observations than those for the clonal tests, and; (5) the two ICBs showed little variation in the relative efficiencies across the missing observation scenarios and test conditions examined. Implications of these results for forest genetic field trials are discussed. For. Sci. 45(3):374-380.

Comparison of Breeding Strategies for Purging Inbreeding Depression via Simulation - Yong‐Bi Fu; Gene Namkoong; John E. Carlson (Conservation Biology, 1998)
Purging deleterious genes in breeding programs, particularly with endangered species, has become of increased interest in recent years, but less attention has been paid to the effectiveness of alternative breeding schemes in these purging programs. We conducted a computer simulation to examine the relative effectiveness of purging deleterious genes in five breeding schemes: continuous selfing, half‐sib mating, and three mixtures of selfing or half‐sib mating alternating over generations. We considered a multiplicative fitness model of lethal, highly detrimental, and detrimental genes affecting viability. We simulated a diploid breeding population of progeny sizes (10, 50, 200) with initial lethal equivalents of 2, 4, 6, 8, and 10 in which each of the five breeding schemes was applied over 10 generations. The patterns of purging, progeny survival, and probability of population extinction were compared among the breeding schemes. Continuous selfing could quickly purge deleterious genes of large effect, especially for increasing progeny fitness, but not necessarily with a low probability of extinction. Continuous half‐sib mating could be as effective in purging as continuous selfing, especially after several generations, but generally with low risk of extinction. The breeding schemes of mixed selfing and half‐sib mating fall mostly between continuous selfing and half‐sib mating schemes in the effectiveness of purging deleterious genes as well as progeny survival and probability of extinction. These results suggest that a mild inbreeding system such as half‐sib mating might be the breeding scheme of choice in breeding programs of endangered species, especially for avoiding increases in extinction probability. Comparación de Estrategias de Reproducción para Eliminar Depresión por Intracruza via Simulación La eliminación de genes dañinos en programas de reproducción, particularmente en especies en peligro de extinción, ha tomado un creciente interés en los últimos años. Sin embargo, poca atención se ha prestado a las investigaciones sobre la efectividad de esquemas alternativos de reproducción en estos programas de purga. Conducimos una simulación por computadora para examinar la efectividad relativa de la purga de genes dañinos en cinco esquemas de cruza (i.e. cruza continua con‐el‐mismo y cruzas de medios‐hermanos, asi como tres mezclas de cruza con‐el‐mismo o cruzas de medios‐hermanos alternando por varias generaciones). Consideramos un modelo de capacidad multiplicativa de genes letales, altamente perjudiciales y perjudiciales afectando la viabilidad. Simulamos la cruza de una población diploide de tamaños de progenie (10, 50, 200) con equivalentes letales de 2, 4, 6, 8 y 10 a los cuales cada uno de los cinco programas de cruza fueron aplicados por mas de 10 generaciones. Los patrones de purga, supervivencia de la progenie y probabilidad de extinción poblacional fueron comparados entre los esquemas reproductivos. Cruza continua con‐el‐mismo podría eliminar rápidamente genes dañinos de largo efecto, especialmente al incrementar la condición de la progenie, pero no necesariamente con una población con baja probabilidad de extinción. Cruza continua de medios‐hermanos podría ser tan efectiva como la anterior en la purga de genes, especialmente despues de varias generaciones, pero generalmente con bajo riesgo de extinción. Los esquemas de cruza mezclados mayormente caen entre uno y otro esquema en cuanto a la efectividad de la purga de genes dañinos, asi como para la supervivencia de la progenie y la probabilidad de extinción. Estos resultados sugieren que un sistema ligero de intracruza como es la cruza de medios‐hermanos podría ser el esquema reproductivo a elegir en programas de cruza de especies en peligro, especialmente para evitar incrementos en la probabilidad de extinción.

Comparison of Breeding Strategies for Purging Inbreeding Depression via Simulation - Yong-Bi Fu; Gene Namkoong; John E. Carlson (Conservation Biology, 1998)